2019
DOI: 10.1186/s40168-019-0685-7
|View full text |Cite
|
Sign up to set email alerts
|

Haem iron reshapes colonic luminal environment: impact on mucosal homeostasis and microbiome through aldehyde formation

Abstract: Background The World Health Organization classified processed and red meat consumption as “carcinogenic” and “probably carcinogenic”, respectively, to humans. Haem iron from meat plays a role in the promotion of colorectal cancer in rodent models, in association with enhanced luminal lipoperoxidation and subsequent formation of aldehydes. Here, we investigated the short-term effects of this haem-induced lipoperoxidation on mucosal and luminal gut homeostasis including microbiome in F344 male rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 74 publications
(84 reference statements)
2
39
0
Order By: Relevance
“…16 These data, and the changes seen in participant faecal microbiome analysis, support previously published data that propose that haem iron, through its impact on mucosal homeostasis, can alter the colonic luminal environment and, hence, the associated microbiome. 17 Strikingly, in a study by Lee et al examining the effect of oral and intravenous iron supplementation on patients with inflammatory bowel disease, 8 oral iron supplementation was associated with decreased abundances of the bacterial species F. prausnitzii, D. formicigenerans and C. aerofaciens; in this study, the reduction in colonic iron was associated with an increase in these exact species, aligning findings with 2 independent approaches. In particular, a depletion of F. prausnitzii has been implicated in several diseases, including fatty liver disease and inflammatory bowel disease, and therapies to augment its abundance would be of potential clinical benefit.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…16 These data, and the changes seen in participant faecal microbiome analysis, support previously published data that propose that haem iron, through its impact on mucosal homeostasis, can alter the colonic luminal environment and, hence, the associated microbiome. 17 Strikingly, in a study by Lee et al examining the effect of oral and intravenous iron supplementation on patients with inflammatory bowel disease, 8 oral iron supplementation was associated with decreased abundances of the bacterial species F. prausnitzii, D. formicigenerans and C. aerofaciens; in this study, the reduction in colonic iron was associated with an increase in these exact species, aligning findings with 2 independent approaches. In particular, a depletion of F. prausnitzii has been implicated in several diseases, including fatty liver disease and inflammatory bowel disease, and therapies to augment its abundance would be of potential clinical benefit.…”
Section: Resultssupporting
confidence: 80%
“… 16 These data, and the changes seen in participant faecal microbiome analysis, support previously published data that propose that haem iron, through its impact on mucosal homeostasis, can alter the colonic luminal environment and, hence, the associated microbiome. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, diet prevalently based on red meat and animal fats promotes dysbiosis with a selection of bacterial species that alter bile acid metabolism, with proinflammatory and prooncogenic effects [40]. A crucial role in the colorectal adenoma risk is also referred to a diet rich in heme iron contained in red meat that leads to modification gut barrier homeostasis and microbiota associated with the selection of bacteria linked to inflammation and colorectal adenoma [41]. Heme iron induces the oxidation of dietary polyunsaturated fatty acids and the consequent production of unsaturated aldehydes, such as malondialdehyde and 4hydroxynonenal (HNE), which are cytotoxic [42].…”
Section: Modifiable Factorsmentioning
confidence: 99%
“…Colon cells harbouring Adenomatous Polyposis Coli (APC) mutations in rats are resistant to apoptosis induced by HNE, suggesting that lipoperoxidation by heme iron confers to these cells a selective survival advantage [70]. Luminal lipoperoxidation is associated with high levels of mucosal inflammation markers, such as the myeloperoxidase activity with ROS production, increased gene expression of interleukin 6 (IL-6) and transforming growth factor β (TGF-β), and enhanced cellular permeability due to reduced expression of the junctional adhesion molecules [41]. e toxicity of the nitrosylated heme iron seems to act for site-specific etiology of colon adenoma.…”
Section: Modifiable Factorsmentioning
confidence: 99%
“…The authors concluded that the stronger Nrf2-dependent antioxidant response could explain the tumor promoting effect of red meat in colorectal carcinogenesis, i.e., by inducing a positive selection of preneoplastic cells [40]. In rats fed a diet supplemented with hemin for 21 days, the lipid peroxidation levels in fecal water were significantly higher than those in fecal water of control rats [41]. These higher luminal lipid peroxidation levels were associated with higher mucosal inflammation markers as revealed by an increased colonic myeloperoxidase activity and an enhanced expression of interleukin-6 and transforming growth factor-β as well as a higher DNA damage in the colonic mucosa of hemin-fed rats when compared to control rats [41].…”
Section: The Role Of Lipid Peroxidation Products In Colon Cancer Dmentioning
confidence: 99%